Balancing contradictory demands during the transition to a business model portfolio for sustainability - Terje Berntsen; Tor Helge Aas; John Arngrim Hunnes (Cogent Business & Management, 2023)
While many firms manage multiple business models concurrently, little is known about how they successfully transition to a portfolio of business models and even less about how this process unfolds in the context of sustainability. In this qualitative in-depth case study, we focus on the transition from a single business model to a portfolio that includes novel sustainable business models and study how an organization manages contradicting demands during this process. Our findings suggest that the transition is a dynamic and iterative transformation process whereby managers navigate contradictory demands by using specific balancing mechanisms, which we identified as bridging and segmenting. We propose a novel model explaining the transition process and offer an understanding of how transitions towards sustainable business models can be navigated and potentially accelerated.
Keywords: 650; Ambidexterity; Business Model Innovation; business Model Portfolio; Contradictory Demands; Sustainability; Transition